Unilateral optic disc oedema as a first sign of ocular toxoplasmosis – case report - Chudoba, Tomasz; Borkowski, Piotr; Sempińska-Szewczyk, Joanna; Filipiak, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Diagnostic procedure for unilateral optic disc oedema needs detailed medical history, careful physical examination and multiple additional tests. We present a very rare case of atypical unilateral anterior optic neuropathy as a sign of ocular toxoplasmosis in a young female. All diagnostic and therapeutic challenges have been discussed.